Immediate hemodynamic and metabolic effects of 7.5% sodium chloride and its association with 6% dextran 70 in hemorragic shock resuscitation. An experimental study in dogs - Meletti, José Fernando Amaral; Braz, José Reinaldo Cerqueira [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP] (My University, 2006)
BACKGROUND AND OBJECTIVES: Dextran associated with 7.5% sodium chloride has positive hemodynamic effects in the long term control of hemorrhagic shock. The objective of this study was to verify whether the association of dextran with 7.5% chloride solution would be advantageous in the immediate hemodynamic evaluation of controlled hemorrhagic shock in dogs. METHODS: This study included 16 dogs submitted to controlled hemorrhage until their mean arterial blood pressure reached 40 mmHg, being maintained at this level for 30 minutes. They were divided in two groups: G1 received 7.5% NaCl and G2 received 7.5% NaCl in 6% dextran 70; in both groups, 4 mL.kg-1 of the solutions were administered for three minutes. Hemodynamic and metabolic parameters were evaluated in four different phases: M1 - 10 minutes after preparation for surgery, M2 - obtained in the middle of the shock phase. M3 - two minutes after the administration of the IV solutions, M4 - 30 minutes after the beginning of the resuscitation. RESULTS: After the resuscitation, there were no significant differences in HR, MAP, PCP, and SVRI. G2 presented the highest CI values in M4. G1 showed the smaller SvO2 values at the end of the experiment; and the C(a-v)O2 was higher in M3 and M4. For both groups, VO2 values increased in M4, and lactate plasma values increased progressively until M3, decreasing in M4. Both groups also presented increased Na plasma values and decreased hematocrit. CONCLUSIONS: G2 showed the best hemodynamic performance, especially 30 minutes after the beginning of resuscitation. Plasma expansion and tissue perfusion were also better with 7.5% NaCl in dextran. © Sociedade Brasileira de Anestesiologia, 2006.
Efeitos hemodinâmicos e metabólicos imediatos determinados pelas soluções de cloreto de sódio a 7,5% e de sua associação ao dextran 70 a 6% na reanimação do choque hemorrágico. Estudo experimental em cães
Keywords: Animals: dogs; Shock: hypovolemic; Volemia: crystalloid expansion, dextran